2018
DOI: 10.1021/acsami.8b00297
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbit[8]uril-Based Giant Supramolecular Vesicles: Highly Stable, Versatile Carriers for Photoresponsive and Targeted Drug Delivery

Abstract: Highly stable giant supramolecular vesicles were constructed by hierarchical self-assembly of cucurbit[8]uril (CB[8])-based supra-amphiphiles for photoresponsive and targeted intracellular drug delivery. These smart vesicles can encapsulate the model drugs with high loading efficiencies and then release them by manipulating photoswitchable CB[8] heteroternary complexation to regulate the formation and dissociation of supra-amphiphiles that cause dramatic morphological changes of the assemblies to achieve remot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 38 publications
1
47
0
Order By: Relevance
“…[68] Angewandte Chemie Minireviews drug delivery vehicle.I nf act, this strategy has been recently exploited for the targeted photo-controlled delivery of doxorubicin from supramolecular vesicles. [69] Other examples of the light-driven Ty pe E-C interconversion have been reported, showing the versatility of the approach for the light-controlled self-assembly of new functional materials,i ncluding hybrid raspberry-like colloids, [70] supramolecular polymeric nanoparticles [71] or polymeric networks. [72] Furthermore,i nar ecent study,J onkheijm and coworkers have used the Ty pe E-C photoswitch for the reversible immobilization of cowpea chlorotic mottle virus nanocages on surfaces (Scheme 19).…”
Section: Reversible Photoswitching Of Cb[8]:bpc:ed Complexesmentioning
confidence: 99%
“…[68] Angewandte Chemie Minireviews drug delivery vehicle.I nf act, this strategy has been recently exploited for the targeted photo-controlled delivery of doxorubicin from supramolecular vesicles. [69] Other examples of the light-driven Ty pe E-C interconversion have been reported, showing the versatility of the approach for the light-controlled self-assembly of new functional materials,i ncluding hybrid raspberry-like colloids, [70] supramolecular polymeric nanoparticles [71] or polymeric networks. [72] Furthermore,i nar ecent study,J onkheijm and coworkers have used the Ty pe E-C photoswitch for the reversible immobilization of cowpea chlorotic mottle virus nanocages on surfaces (Scheme 19).…”
Section: Reversible Photoswitching Of Cb[8]:bpc:ed Complexesmentioning
confidence: 99%
“…Such vesicles have been successfully employed to encapsulate fibroblast growth factor, extending its bioactivity without the necessity of excipients such as heparin . Hetero‐ternary complexes involving the host–guest CB[8]‐maleimide‐modified MV and azo‐dyes have been self‐assembled on the surface of giant vesicles to be used as models of optically active drug carriers for delivery to specific targets . On the other hand, Das and co‐workers have established that different aromatic amino acids can form vesicles through ternary complexes with CB[8] and an amphiphilic viologen.…”
Section: Towards Dynamic Supramolecular Materialsmentioning
confidence: 99%
“…The data revealed that vesicle(C 3 ) was found to be the most efficient in loading DOX (10.5 %) (Figure ). Since all the vesicles reported herein were found to be stable up to pH 3 (Figure S8, supporting information), we explored a well‐known vesicle destroyer (Triton X‐100) in order to deliver the encapsulated drug in a stimuli responsive fashion. DLS data of all the vesicles in presence of Triton X‐100 (5 μL) showed significantly smaller particle size (≈10 nm) indicating disruption of the vesicular structures (Figure S9, supporting information).…”
Section: Resultsmentioning
confidence: 99%